Seroconversion of 2009 pandemic influenza A (H1N1) vaccination in kidney transplant patients and the influence of different risk factors. Issue 6 (18th October 2013) - Azevedo, L.S.; Gerhard, J.; Miraglia, J.L.; Precioso, A.R.; Tavares Timenetsky, M.dC.S.; Agena, F.; Gamba, C.; Shikanai Yasuda, M.A.; David‐Neto, E.; Pierrotti, L.
Abstract Background Influenza may present a high morbidity and mortality in solid organ transplanted patients (SOTP). Annual influenza virus vaccine is recommended for SOTP. However, low levels of seroconversion in SOTP have been reported. The aim of this study was to evaluate the immunogenicity of 2009 pandemic influenza A (H1N1) – A(H1N1)pdm09 – vaccine in kidney transplant patients and to analyze which features might affect seroconversion. Methods This study was conducted from March to August 2010 at the Renal Transplantation Unit of University of São Paulo, Brazil. A total of 85 renal transplant patients attending the outpatient unit received one 15‐μg intramuscular dose of A(H1N1)pdm09 influenza vaccine (reassortant vaccine virus A/California/7/2009 [NYMC X‐179A]). Blood samples were collected immediately before and 21 days after the vaccine was given. Antibody response was measured by the standard hemagglutination‐inhibition (HI) assay. The primary immunogenicity endpoint for this study was seroconversion in previously seronegative patients (HI titers <1:40), and the secondary endpoint was the identification of features that could affect seroconversion in this population. Results Five (5.9%) patients presented HI titers prevaccination ≥1:40 and were excluded from further analysis. Seroconversion in previously negative patients occurred in 27 (34%) of 80 patients. Prevaccination HI titers geometrical mean was 5.8 and postvaccination 19.6 (ratio 3.4). Significant seroconversion rate factors were female gender, non‐Caucasian ethnicity, and post‐transplant time before vaccination. No impact was seen on seroconversion for age, donor type, tacrolimus and cyclosporine blood levels, renal function, or blood lymphocyte counts. Mycophenolate (MPA) showed a lower rate of seroconversion when compared with azathioprine. Tacrolimus and cyclosporine had similar seroconversion rates. Sirolimus use was associated with the highest rate of seroconversion, although these patient numbers were low. Immunosuppresssion containing MPA was considerably less effective in seroconversion than drug combinations with no MPA. Patients receiving sirolimus had more chance of seroconversion. HI titers geometric means pre/post vaccine were as follows: MPA (n = 56): 5.8/12.8; tacrolimus (n = 50): 5.9/16.2; cyclosporine (n = 18): 5.4/24.2; azathioprine (n = 19): 6.2/51.6; and sirolimus (n = 6): 8/80. By univariate analysis, being female and non‐White were variables associated with 3.3 times more chance of seroconversion than being male and White. In the multivariate analysis, the variables remaining in the model showed similar hazard ratios. Conclusions In this study, the monovalent A(H1N1)pdm09 influenza vaccine demonstrated low rates of seroconversion, particularly in patients on MPA, but with potentially higher response rates in patients on sirolimus.